2014
DOI: 10.1038/ng.2895
|View full text |Cite
|
Sign up to set email alerts
|

Dense genomic sampling identifies highways of pneumococcal recombination

Abstract: Evasion of clinical interventions by Streptococcus pneumoniae occurs through selection of non-susceptible genomic variants. Here we use genome sequencing of 3,085 pneumococcal carriage isolates from a 2.4 km2 refugee camp to enable unprecedented resolution of the process of recombination, and highlight its impact on population evolution. Genomic recombination hotspots show remarkable consistency between lineages, indicating common selective pressures acting at certain loci, particularly those associated with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
511
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 368 publications
(538 citation statements)
references
References 44 publications
22
511
5
Order By: Relevance
“…While non-typeable pneumococcal isolates are more commonly associated with carriage rather than invasive disease, non-typeable pneumococci has been isolated from children with IPD. 17,30,31 Furthermore, recent evidence suggests that non-typeable pneumococci have high genetic recombination potential leading to the possibility of spreading antibiotic resistance making their identification important for surveillance studies 32,33,34 Approximately 50% of the pneumococcal isolates found during our study were non-PCV13 serotypes (with an additional 44% of the types being non-typeable). One-third of the a CLSI breakpoints used for determination of susceptibility ( 2 mg/mL penicillin, 2 mg/mL cefotaxime, 2 mg/mL trimethoprim-sulfamethoxazole).…”
Section: Discussionmentioning
confidence: 90%
“…While non-typeable pneumococcal isolates are more commonly associated with carriage rather than invasive disease, non-typeable pneumococci has been isolated from children with IPD. 17,30,31 Furthermore, recent evidence suggests that non-typeable pneumococci have high genetic recombination potential leading to the possibility of spreading antibiotic resistance making their identification important for surveillance studies 32,33,34 Approximately 50% of the pneumococcal isolates found during our study were non-PCV13 serotypes (with an additional 44% of the types being non-typeable). One-third of the a CLSI breakpoints used for determination of susceptibility ( 2 mg/mL penicillin, 2 mg/mL cefotaxime, 2 mg/mL trimethoprim-sulfamethoxazole).…”
Section: Discussionmentioning
confidence: 90%
“…This whole genome alignment allowed calculation of SNP and INDEL rates across recent S. pneumoniae evolutionary history. We used previously determined parameters for the rate of codon evolution 14 , relative rate of SNPs to indels in coding regions 15 , rates of gene loss and horizontal gene transfer 16 when running the simulation. We then used ALF with these parameters to simulate the evolution of coding sequences from the root genome along the given phylogeny.…”
Section: Methodsmentioning
confidence: 99%
“…In large-scale genome sequencing of bacterial strains, we see thousands of recombination events [15], and indeed, on occasion, explaining phenotypes requires methods that explicitly need to account for and remove vertical transmission signals [16]. One thousand eubacterial genes have flowed into the stem lineage of halophilic Archaebacteria and identification of this important evolutionary event required the modelling of horizontal, rather than vertical gene flows [17].…”
Section: Introductionmentioning
confidence: 99%